Comparative study of predisposition to thrombosis with administration of known systemic hemostatic agents and fibrin monomer in the experiment - V. M. Vdovin; I. I. Shakhmatov; A. P. Momot (Бюллетень сибирской медицины)
Aim. To compare predisposition to thrombosis caused by administration of known systemic hemostatic agents and fibrin monomer under the conditions of normal coagulation versus drug-induced hypocoagulation in the experiment.Materials and methods. The prothrombotic effect of intravenous (IV) administration of various systemic hemostatic agents was compared in a series of in vivo experiments. These agents included fibrin monomer (FM) (0.25 mg / kg), prothrombin complex concentrate (PCC) (40 IU / kg) or recombinant factor VIIa (rFVIIa) (270 mcg / kg). The studies were conducted under the conditions of hypocoagulation induced by the administration of warfarin (per os at a dose of 0.4–0.5 mg / kg / day for 14 days) or dabigatran etexilate (per os at a single dose of 15–20 mg / kg). Hemostatic system parameters were evaluated using thromboelastometry and calibrated automated thrombography.Results. It was found that PCC reversed anticoagulant effects and led to an overcompensated increase in the density characteristics of the blood clot along with an excessive increase in thrombin generation in the groups of animals with warfarin-induced coagulopathy. The use of PCC and rFVIIa in the groups of animals with dabigatran-induced hypocoagulation also resulted in an increase in blood thrombogenic properties. In the administration of PCC, it was manifested though an increased D-dimer level and in administration of rFVIIa – through an increase in the clot density characteristics. At the same time, replacement of these hemostatic agents with FM did not affect the hemostatic system parameters.Conclusion. FM at a dose of 0.25 mg / kg, as opposed to PCC and rFVIIa, is safer in terms of the risk of thrombosis.